The Value of Global Diversity in Elementary School Education (Literature Review) - Masriyah, Masriyah; Dessy Setyowati; Suriyana, Suriyana (PT. ALHAFI BERKAH INDONESIA, 2025)
This study aims to analyze the value of global diversity in elementary school learning, which is based on the ability of students to adapt to life in the current era of globalization. Students will grow into a diverse nation, without losing their national identity and able to appreciate their culture, but without closing themselves off from outside influences. The method used in this study is descriptive qualitative and documentation as data collection techniques sourced from primary data in the form of 10 articles. The instrument used is an analysis sheet with non-statistical analysis techniques, the results of which are then described. The results of the analysis of the 10 articles are that global diversity is one of the dimensions of the Pancasila student profile. Global diversity has four elements, namely recognizing and appreciating culture with an availability percentage of 76%, the element of communication and interaction between cultures with an availability percentage of 85%, the element of reflection and responsibility towards diversity experiences with an availability percentage of 60%, and the element of social justice with an availability percentage of 33%. The Pancasila profile of global diversity will shape intelligent students with character in accordance with the values contained in diversity and improve human resources not only nationally but also internationally. The Pancasila learner profile is a set of character traits and competencies that students are expected to achieve by adhering to the noble values of Pancasila.